Gestação subsequente à perda perinatal: análise dos resultados de um programa de pré-natal psicológico - Martins, Marley Carvalho Feitosa (2024)
This thesis is the result of a Mixed Method study whose objective was to analyze the results of the psychotherapeutic intervention “Psychological Prenatal” developed to prevent the increased risk of physical and emotional complications in subsequent pregnancy. The study was carried out virtually, from April 2021 to November 2023, in two phases: I) qualitative research, with a sample of 30 pregnant women (Case Group) with a history of perinatal losses; and II) quantitative analysis of the factors involved in pregnancy subsequent to perinatal losses to which 30 women with a history of perinatal losses, with another live-born child after perinatal loss (Control Group) were added. Both groups underwent interviews covering sociodemographic characteristics, obstetric history of the previous loss and neonatal characteristics of the subsequent pregnancy. The PNP intervention consisted of five sessions during pregnancy and one 30 days after delivery. The themes of each session were contextualized in an interactive way, facilitating the free expression of feelings and reports of experiences, submitted to interpretative thematic analysis. Symptoms of complications of grief and postpartum depression were analyzed, comparing the results of both groups using the Odds ratio (p≤0.05). The persistent prediction of symptoms of depression (55.6% p=0.027) and complicated grief (42.3% p=0.049) in the Control Group is highlighted. And, a significant reduction in the level of grief in the Case Group, during (42.9%) and after the intervention (17.9%). It was shown that mental health problems have a negative impact on pregnancy outcomes and fetal development, increasing the risk of adverse outcomes, such as prematurity, which was highly significant in this study (p=0.020), with a prevalence of 30.0% in the Control Group and 6.7% in the Case Group. Thematic analysis revealed that the lack of elaboration of mourning for the lost baby activates painful emotions in the subsequent pregnancy, compromising the development of maternal attachment to subsequent baby and self-confidence in the ability to maintain a successful pregnancy. All of this was reflected in self-protection mechanisms: emotional cushioning, hypervigilance and negativity (“expecting the worst”). The results suggest that the PNP intervention developed in this study for post-loss pregnancy acted positively by providing strategies for early recognition of symptoms and treatment of perinatal mood disorders, positively impacting pregnancy, fetal development and parenting.